Supplementation of Zinc Sulphate Decrease for Cytokine Levels TNF-Α, IL-1β and IL-6 in Multibacillary Leprosy Patients - Joko Kurnianto; Hertanto W S; Prasetyowati Prasetyowati; Suharyo H. S. (Humanistic Network for Science and Technology (HNST), 2019)
Background: The role of zinc as an anti-oxidant and anti-inflammatory has been widely proven, this substance is relatively inexpensive and easily available to the public. Serum zinc levels of leprosy patients and patients with leprosy reactions are lower compared to healthy people, and proinflammatory cytokines including TNF-α, IL-1β and IL-6 play a role in the mechanism of leprosy reactions. Research on the effect of zinc supplementation on leprosy sufferers who have not experienced a reaction has not been done. Objective: To analyze the effect of 40 mg / day dose of zinc sulphate supplementation for 12 weeks on the levels of proinflammatory cytokines levels TNF-α, IL-1β and IL-6 in type MB leprosy patients. Method: This is an experimental study using a randomized control group pretest and posttest design. The study participants were MB patients with 121 patients who did not experience a leprosy reaction, the sample was taken randomly as many as 31 patients as a supplementation group (treatment), and 31 patients as Control group. BMI measurements, food intake by re-call method, Hb level using Hematology Analyzer, serum zinc levels using Atomic Absorption Spectrophotometry (AAS) method, TNF-α, IFN-γ, and IL-1β levels used the ELISA method. Data were analysed using chi-square and t-tests. Results: Zinc sulfate supplementation dose of 40 mg / day for 12 weeks in type MB leprosy patients was able to maintain a decrease in zinc levels of 1.22 pg / dL higher than leprosy patients who did not receive zinc supplementation, reduce levels of IL-1β (p=0.032). However, statistically there is insufficient evidence to reduce levels of TNF-α (p=0.063) and IL-6 (p=0.389) and risk factors. Conclusion: The study confirmed that 40 mg / day supplementation of zinc sulfate for 12 weeks in type MB leprosy patients able to maintain a decrease in serum zinc levels, reduce IL-1β levels. Keywords: Supplementation, Cytokines, Type MB leprosy